Stress Strain Relationship of Polymer Modified No-Fine Concrete - S. Al-Numan, Bayan (Iraqi Journal of Civil Engineering, 2005)
Abstract The use of no fines concrete in construction increased especially during and after 1970s. New concrete is obtained from no-fines concrete in this research by adding Styrene Butadiene Rubber (SBR) Polymer as a ratio of cement content. This research includes the study of the effect of SBR polymer on stress-strain relationship of concrete under compression. The concrete mixes by weight were (1:7, 1:6, 1:5, and 1:4) cement / aggregate (C/A). The polymer was added as percentages by weight of cement as (5, 7.5 and 10%). Rreference mixes were made for every case. A new mathematical model for both ascending and descending portions is suggested in this research and discussed. The area under the stress strain curve was found in polymer modified no-fines concrete to be greater than reference concrete and was increased with polymer / cement ratios (P/C). The suitability of no fine polymer concrete to be used in structural members has been affirmed in this research especially for (1:4 and 1:5) C/A polymer mix.